Analysis of non-uniform polygonal cross-sections for thin-walled functionally graded straight and curved beams. (1st January 2021) - Nguyen, Tan-Tien; Nguyen, Ngoc-Linh; Lee, Jaehong; Nguyen, Quoc-Hung
Highlights: Thin-walled FG beam analysis regarding non-uniform polygonal cross-sections. Considering higher-order warping and distortion as well as material anisotropy. Applicable to both functionally graded straight and curved beams. Interaction of material distribution, skin-core-skin ratio on behaviors. Abstract: The paper adequately presents an analysis of thin-walled functionally graded straight and curved beams for general non-uniform polygonal cross-sections. In order to mathematically model a complex beam which property information in both material distribution and geometric continuity need to be collected from multiple patches through blade thickness and each cross-section, a higher-order approach has been adopted. Subsequently, the higher orders of warping, coupling distortion including bending, torsion as well as Poisson's distortion were fully taken into account. The anisotropy of materials with its effects are then also included. Beam frame modal which each edge on a cross-section is generally considered as multi-separated beams has found to be extremely compatible that well captures all behaviors of the beam. As a result, the study allows a blended coupling of closed-section beam-shells on different curvatures. Various examples were conducted to illustrate the performance and accuracy also the computational efficiency of the method where several compared results coming from ABAQUS modeling.